​​Curriculum Analytics of SDG Integration in UNIMAS Academic Programmes - Dayang Nur Salmi Dharmiza, Awang Salleh; Nur Tahirah, Razali; Anna, Andrew; Devagi, Kanakaraju; Mohd Farid, Atan (2025)
Since the introduction of the United Nations Sustainable Development Goals (SDGs), higher education institutions play vital roles preparing future graduates for global challenges by integrating SDG elements into the curriculum that meets the purpose of Education for Sustainable Development (ESD). This study comprises the SDG integration in 47 undergraduate programmes and 25 postgraduate programmes across 10 faculties in Universiti Malaysia Sarawak (UNIMAS). Our academic management system has recorded the mapping of SDG integration in courses offered in the programmes as part of the learning units or course learning outcomes (CLO). This paper presents the integration distribution of all 17 SDGs on UNIMAS’ academic programmes by descriptive statistics and a treemap to visualize the SDG coverage magnitude in offered courses, while at the faculty level, heat maps illustrate relevant SDG variations based on disciplines. The findings show that all SDGs were integrated into the curriculum; however the coverage is uneven, with SDG4 (Quality Education), SDG3 (Good Health and Well-being) and SDG9 (Industry, Innovation and Infrastructure) dominating the SDG integration coverage. Other SDGs, such as SDG2 (Zero Hunger) and SDG6 (Clean Water and Sanitation) had the least coverage, with only 4% integration in the total course offered, indicating potential gaps. This study concludes by recommending enhanced SDG coverage through greater faculty involvement in interdisciplinary projects and stronger involvement with both the community and industry.